Buddhism is not what you think : finding freedom beyond beliefs - Hagen, Steve, 1945- (San Francisco : HarperSanFrancisco, 2003)
"Steve Hagen penetrates the most essential and enduring questions at the heart of the Buddha's teachings: How can we see the world as it comes to be in each moment, rather than merely as what we think, hope, or fear it is? How can we base our actions on Reality, rather than on the longing and loathing of our hearts and minds? How can we live lives that are wise, compassionate, and in tune with Reality? And how can we separate the wisdom of Buddhism from the cultural trappings and misconceptions that have come to be associated with it?" "Drawing on down-to-earth examples from everyday life and stories from Buddhist teachers past and present, Hagen tackles these fundamental inquiries with his trademark lucid, straightforward prose. The newcomer to Buddhism will be inspired by this accessible and provocative introduction, while those more familiar with Buddhism will welcome this hands-on guide to understanding what it is to be awake."--BOOK JACKET.
33. Forsaking Understanding -- 34. How Do We Know? -- 35. Nothing Else -- 36. It's Not a Matter of Belief -- 37. How to Be Liberated on the Spot -- 38. This Will Never Come Again -- 39. The Elixir of Immortality -- 40. Ice Forming in Fire -- 41. Purely Mind -- 42. Time and Now -- 43. Enlightenment -- Epilogue: Reality Is Not What You Think.
Keywords: Buddhism -- Doctrines; Truth (Buddhism)